Synbiotic Effects of Fermented Rice on Human Health and Wellness: A Natural Beverage That Boosts Immunity - Fuloria, Shivkanya; Mehta, Jyoti; Talukdar, Manash Pratim; Sekar, Mahendran; Gan, Siew Hua; Subramaniyan, Vetriselvan; Rani, Nur Najihah Izzati Mat; Begum, M. Yasmin; Chidambaram, Kumarappan; Nordin, Rusli; Maziz, Mohammad Nazmul Hasan; Sathasivam, Kathiresan V.; et al. (Frontiers in Microbiology, 2022)
Fermented foods have been an important component of the human diet from the time immemorial. It contains a high amount of probiotics that have been associated to a wide range of health benefits, including improved digestion and immunity. This review focuses on the indigenously prepared prebiotic- and probiotic-containing functional fermented rice (named Xaj-pani) by the Ahom Community from Assam, in Northeast India, including all the beneficial and potential effects on human health. Literature was searched from scientific databases such as PubMed, ScienceDirect and Google Scholar. Glutinous rice (commonly known as bora rice of sali variety) is primarily employed to prepare beverages that are recovered through the filtration process. The beer is normally consumed during religious rites, festivals and ritual practices, as well as being used as a refreshing healthy drink. Traditionally, it is prepared by incorporating a variety of medicinal herbs into their starter culture (Xaj-pitha) inoculum which is rich in yeasts, molds and lactic acid bacteria (LAB) and then incorporated in alcoholic beverage fermentation. The Ahom communities routinely consume this traditionally prepared alcoholic drink with no understanding of its quality and shelf life. Additionally, a finally produced dried cake, known as vekur pitha act as a source of Saccharomyces cerevisiae and can be stored for future use. Despite the rampant use in this community, the relationship between Xaj-pani’s consumption, immunological response, infectious and inflammatory processes remains unknown in the presence of factors unrelated or indirectly connected to immune function. Overall, this review provides the guidelines to promote the development of prebiotic- and probiotic-containing functional fermented rice that could significantly have an impact on the health of the consumers.